PERAN GERAKAN LITERASI SEKOLAH DALAM MENINGKATKAN MOTIVASI DAN MINAT BACA SISWA - ROZIA AFRIA HUSNA (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2022)
This research is motivated by the low interest in reading students in the world of education, especially at the elementary level. This low interest in reading has triggered the government through the Ministry of Education and Culture to hold a School Literacy Movement which is integrated into the curriculum. With the hope of increasing students' interest in reading and becoming a center of motivation for lifelong learning. The purpose of this research is to describe the role of the school literacy movement in increasing students' motivation and interest in reading. This study uses a descriptive qualitative approach. The research subjects were fourth grade students at SDN 2 Suryawangi. Data collection techniques in the form of interviews with school principals, librarians, teachers for grade IV, grade IV students, observation, and documentation. Based on the results of the study, it was shown that the implementation of the school literacy movement at SDN 2 Suryawangi implemented a strategy in the form of 15-minute reading activities in the classroom reading corner and mandatory visits for each class to the library. This 15-minute reading activity is carried out every day in class as an effort to make reading habits and visits to the library as a form of motivation for students to want to read. In influencing students' reading interest, three stages of the implementation of the school literacy movement are carried out including the habituation stage, the development stage, and the learning stage. The supporting factor is the active role of all school members and adequate infrastructure, while the obstacle is the different interests of children so that it is the teacher's job to motivate students to have the habit of reading. ABSTRAKPenelitian ini dilatarbelakangi karena rendahnya minat baca siswa dalam dunia pendidikan khususnya pada tingkat dasar. Minat baca yang rendah ini memicu pemerintah melalui kemendikbud mengadakan Gerakan Literasi Sekolah yang diintegrasikan ke dalam kurikulum. Dengan harapan dapat meningkatkan minat baca siswa dan menjadi pusat motivasi untuk belajar sepanjang hayat. Tujuan peneltian ini adalah untuk mendeskripsikan peran gerakan literasi sekolah dalam meningkatkan motivasi dan minat baca siswa. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Subjek penelitiannya adalah peserta didik kelas IV SDN 2 Suryawangi. Teknik pengumpulan data berupa wawancara dengan kepala sekolah, pustakawan, guru wali kelas IV, siswa kelas IV, observasi, dan dokumentasi. Berdasarkan hasil penelitian menunjukkkan bahwa pelaksanaan gerakan literasi sekolah di SDN 2 Suryawangi menerapkan strategi berupa kegiatan membaca 15 menit di pojok baca kelas dan kunjungan wajib setiap kelas ke perpustakaan. Kegiatan membaca 15 menit ini dilakukan setiap hari di kelas sebagai upaya melakukan pembiasaan membaca dan kunjungan ke perpustakaan sebagai bentuk motivasi siswa untuk mau membaca. Dalam mempengaruhi minat baca siswa dilakukan tiga tahapan pelaksanaan gerakan literasi sekolah diantaranya yaitu tahap pembiasaan, tahap pengembangan, dan tahap pembelajaran. Faktor pendukungnya yakni peran aktif seluruh warga sekolah dan sarana-prasrana yang memadai, sedangkan yang menjadi hambatannya yakni minat anak yang berbeda-beda sehingga menjadi tugas guru untuk memotivasi siswa memiliki kebiasaan membaca.